Sugars that Glow in the Dark: Fluorescent Tagged Glucose Bioprobes and their Facilitation of the Drug Discovery Process - Um, JungIn; Lee, JiHyung; Jung, Da-Woon; R. Williams, Darren (Current Medicinal Chemistry, 2015)
Fluorescent tagged glucose probes offer an attractive alternative to traditional, radioactive based methods for measuring glucose flux in biological systems. Thus, it could be envisaged that these probes would be widely used. However, this is not the case and, since their development in the mid-1980s, fluorescent tagged glucose bioprobes are relatively underutilized in biological research compared to radioactive methods, with only a small number (<10) publications per year using these probes. However, within the past five years there has been a surge in research activity. By the year 2012, numerous novel probes were developed and the number of research publications dramatically increased. This was especially relevant for drug discovery applications related to cancer, neurology and diabetes research. In this review article, we discuss the research impact of these bioprobes and assess which probes have been most successfully applied to drug discovery applications. Significantly, we also discuss latest research that shows the potential of these probes to be used for drug discovery in animal models and their application to in vivo-based drug validation. Overall, we hope that this review will raise awareness of the research opportunities that these probes offer to the drug discovery research community.
Keywords: Anti-cancer